Influence of borehole trajectory and pressure on the characteristics of drilling induced fractures - Lei, Yushun; Wang, Jiayu; Zhu, Zihan; Li, Muyuan; Zhao, Xinwei; Gao, Xiangsen; Zhang, Mingming (Frontiers in Earth Science, 2025)
Research on the identification and classification of drilling-induced fractures plays a critical role in clarifying the mechanisms of wellbore instability and drilling fluid loss, while also supporting the analysis of imaging logging data and reservoir evaluation. In this study, a prediction model for the occurrence of drilling induced fractures is established by using linear elastic wellbore stress model combined with the tensile failure criterion of wellbore surrounding rock. The influences of engineering parameters, specifically borehole trajectory and bottom-hole pressure, on the distribution of principal stresses around the wellbore, as well as the angle between drilling-induced fractures and the borehole axis are investigated. The findings reveal that the induced fractures exhibit a highly organized pattern, typically forming at 180° intervals with a nearly symmetrical, downward-diffusing arrangement. This pattern provides a solid theoretical basis for the identification and classification of these fractures. In addition, under low bottom-hole pressure, the well tends to form feather-shaped induced fractures. As the pressure of the liquid column increases, the angle between these fractures and the borehole axis decreases while their length expands, eventually evolving into a “J”-shaped fracture. Accurate detection and identification of such induced fractures are crucial for reliably interpreting fracture networks and evaluating reservoirs in unconventional oil and gas fields.